PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KECAKAPAN SOSIAL (SOCIAL SKILLS) DAN HASIL BELAJAR IPA SISWA KELAS VIIIE DI SMP NEGERI 12 YOGYAKARTA TAHUN AJARAN 2012/2013 - Rizky Syafika; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
This research was to improve social skills and the result of scientific of students study with aplication of cooperative learning model Teams Games Tournament (TGT) type. This was because there was learning problem in the class of VIII E Junior High School 12 Yogyakarta. That was 1) the result of scientific of students study was low; 2) students antusiasm in the learning activity was low; 3) interaction student with student and student with teacher was low; 4) students was pasive; and 5) the students social skills in the case of empatic, cooperative, and solidarity communication was low. The learning metode that was applied was the result of class action. In this result teacher o researcher and to be observer. The subject o this research was the student o class VIII E Junior High School 12 Yogyakarta which has 32 students. The object this research was coperative learning model TGT, social skills, and the result of students study. After using cooperative learning model TGT, this research was down in 2 cycle ang it every cycle consist of planning, acting, observation, and reflection. The technic data collection through observation sheet, interview, westionair, field note, test, and documentation. The research result indicated that social skills ang the result of scientific students study can improve after giving action. Social skills had increase which was indicated with by its appearing student social skills in every cycle as case of empatic, cooperative, and solidarity skills. The improvement result of scientific student amount was achieve minimum thoroughness criteria > 65% and improvement average at evaluation value in every cycle it was from 70,14 at first cycle to be 84,38 at second cycle. The efforts was down the teacher need impove assistance on group, study group with intensive in order to the student can to cooperative, to empatic, and to solidarity, and the teacher need giving motivation in order to students have believe in with capability students.